2021
DOI: 10.1101/2021.02.08.430295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insight into substrate processing and allosteric inhibition of human p97

Abstract: p97, also known as valosin-containing protein (VCP), processes ubiquitinated substrates and plays a central role in cellular protein homeostasis. Mutations in human p97 are associated with multisystem proteinopathy (MSP), a dominantly inherited degenerative disorder that can affect muscle, bone and the central nervous system. It is also a drug target for cancer therapy with various inhibitors developed over the past decade. Despite significant structural insights into the fungal homologue of p97, Cdc48, little… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(122 reference statements)
1
4
0
Order By: Relevance
“…Our structures show p97 loaded with the SPI complex at a defined position on the N-domain in the act of translocating a segment of I3. The density map (Figure 1a-c and Supplementary Figure S1a) confirms a conserved peptide threading mechanism previously proposed for p97 and yeast Cdc48 (Cooney et al, 2019; Pan et al, 2021; Twomey et al, 2019; Xu et al, 2022). Both D1 and D2 domains of p97 are in the staircase configuration with subunit A on top, followed by subunits B, C and D in a clockwise manner to subunit E at the bottom (Figure 1a and b).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Our structures show p97 loaded with the SPI complex at a defined position on the N-domain in the act of translocating a segment of I3. The density map (Figure 1a-c and Supplementary Figure S1a) confirms a conserved peptide threading mechanism previously proposed for p97 and yeast Cdc48 (Cooney et al, 2019; Pan et al, 2021; Twomey et al, 2019; Xu et al, 2022). Both D1 and D2 domains of p97 are in the staircase configuration with subunit A on top, followed by subunits B, C and D in a clockwise manner to subunit E at the bottom (Figure 1a and b).…”
Section: Resultssupporting
confidence: 83%
“…The SPI structure is best resolved on subunit B, making that state the most informative. Previous structural studies have used cryo-EM to reveal the spiral conformation of p97 with a substrate trapped in the pore (Cooney et al, 2019; Pan et al, 2021; Twomey et al, 2019; Xu et al, 2022), but have not revealed a loading complex with the adaptor proteins delivering the substrate to p97 for protein complex disassembly. Our structure of p97 with a loaded substrate complex on the N-domain reveals unanticipated new principles of how a substrate is positioned and engaged onto p97 with the help of the adapter leading to dissociation of one subunit while sparing the other components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NMS-873 is thought to bind to the linker domain between the D1 and D2 ATPase domains of p97, which stabilizes D2-ADP bound p97 [63]. We performed docking study to investigate the binding mode of NMS-873, which was proposed in Figure 4B [64]. Bastola et al validated the binding site of NMS-873 by the mutations at nearby residues, which abrogated or significantly reduced the activity of NMS-873 [65].…”
Section: Dibenzylquinazolinesmentioning
confidence: 99%